Investors matter when prices are dispersed: the effects of investor activities on housing price dispersion - Ziqing Yuan; K. W. Chau; Xian Zheng (Humanities & Social Sciences Communications)
Abstract Housing price dispersion highlights the individual differences in capital gains by capturing the varying prices among comparable properties. We examine the impact of investors’ activities on housing price dispersion within the Hong Kong private housing market, based on micro-level transactions. Our results indicate that investors’ activities can significantly lower price dispersion in housing markets, even after accounting for trading volumes. The reduction effect of investment activities on price dispersion varies across boom-bust cycles, being more pronounced in cooler markets. We address the roles of housing investors in facilitating the price discovery process and reducing price dispersion by providing liquidity and mitigating information asymmetry. This suggests that well-informed investors can play a welfare-enhancing role by improving information efficiency. We also demonstrate that nearby investment activities can indirectly influence local price dispersion through information spillover effects. Our findings have profound implications for facilitating information efficiency and the potential for reducing price dispersion.